Connecting orchestral conductors' interpretational intentions to conducting movement kinematics: a mixed-methods approach using Deviation Point Analysis - Huang, Yu-Fen (The University of Edinburgh, 2018)
During orchestral performance, conductors play a role in which they provide their interpretations of the musical composition, communicating these interpretational intentions via their body movement. Pedagogical sources propose movement emblems for stock actions by which a conductor may deliver compositional and interpretational features in conducting practise. This thesis reports a mixed-methods study which provides empirical observations on the kinematic features evident in conducting practise, and which aims to explore the connection between such movements with compositional features and conductors’ interpretative intentions. Six conductors’ interpretational intentions were collected in interviews, and their conducting movements were recorded using a Qualisys motion capture system, while they worked on excerpts of repertoire by Mozart, Dvořák, and Bartók with a small string ensemble. In the interviews, conductors reported their general thoughts and beliefs about conducting. They were also prompted to identify the compositional events which they sought to highlight in their conducting, and to describe the conducting strategies they intended to use to highlight these musical events. The resulting qualitative data were thematically analysed. The conductor-identified compositional features were also used to guide kinematic investigations, using an innovative analysis method original to this project, Deviation Point Analysis (DPA). Conductors’ movements are described using four dependent variables of baton tip (movement distance, speed, acceleration, and jerk). Results are reported for two-way repeated measures ANOVAs (repertoire x trial), and for t-tests revealing significant differences between cross-correlation coefficients for within-conductor trial pairs and between-conductor trial pairs. Further examination of the data using DPA serves to distinguish time-points with observable kinematic deviations from the conducting trials. These kinematic deviations were compared with conductors’ stated intentions. Prominent clusters of kinematic deviations were seen to be associated with key musical events which conductors intended to emphasize temporal, melodic, dynamic, and instrumental aspects. Minor clusters of kinematic deviations were seen to be connected with interpretational intentions in a less stable manner, some occurring remotely from the conductor-identified locations. DPA method and findings are fully reported. The implications, advantages and limitations of this novel analysis approach are also discussed.
Keywords: conducting movement; kinematics; musical structure; musical interpretation